Kinerja Bisnis UMKM Kuliner Kota Semarang dikaji oleh Literasi Keuangan, Pembayaran Digital, Penggunaan E-Commerce dan Sistem Informasi Akuntansi - Selma Khoirunnisa Nirmala; Andalan Tri Ratnawati; Sri Suyati; Agung Wibowo (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2025)
MSMEs are a major component of a country's economy. The large contribution of MSMEs to economic development in Indonesia requires MSME players to keep trying and always be ready to compete with other MSMEs. This study aims to determine the effect of financial literacy, digital payments, use of e-commerce and accounting information systems on the business performance of culinary MSMEs in the city of Semarang. The population of this study amounted to 98 culinary MSMEs, sampling using purposive sampling method with the criteria of using digital payments, using e-commerce and accounting information systems. The data was analyzed using multiple linear regression analysis with JASP software. The results of this study indicate that the variables of e-commerce usage and accounting information systems have a positive and significant impact on business performance, so that any increase in these variables will improve MSME business performance. The financial literacy variable has a positive and insignificant effect on business performance, so it is necessary to increase the financial literacy of business actors. Meanwhile, the digital payment variable has a negative and insignificant impact on business performance, indicating a lack of understanding of MSME actors and consumers of the use of digital payments.